A Test of the Reciprocal-Effects Model of Academic Achievement and Academic Self-Concept in Regular Classes and Special Classes for the Gifted. (April 2017) - Preckel, Franzis; Schmidt, Isabelle; Stumpf, Eva; Motschenbacher, Monika; Vogl, Katharina; Schneider, Wolfgang
According to the reciprocal-effects model (REM), prior academic self-concept (ASC) has a positive effect on subsequent achievement beyond what can be explained in terms of prior achievement and vice versa. The present study investigated the REM for students studying in special classes for the gifted compared to students studying in regular classes. The sample included 283 students from 14 special classes for the gifted and 639 students from 26 regular classes from seven high-track schools of the German secondary school system ("Gymnasium"). Students' math achievement (grades and standardized achievement tests) and their ASC in math were assessed four times from the beginning of Grade 5 to the middle of Grade 7. Reciprocal relationships between ASC and academic achievement were positive and comparable across class types, confirming the validity of the REM.